Pemanfaatan Limban Kulit Durian Menjadi Briket Di Desa Sambirejo Kecamatan Wonosalam Kabupaten Jombang - Dhian Satria Yudha Kartika; Pandu Fajar Pramudya; Fajar Tirto Sajiwo; Faris Dwi Kuncoro; Immanuel Toga Raja Hasibuan; Fadhillah Azka Yasjudan (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
The PKK Women's Group in Sambirejo Village, Wonosalam District, Jombang Regency has the potential to produce briquettes from durian peel waste. This is supported by the large amount of waste waste that is wasted. The use of durian peel waste in Sambirejo Village has never been done before. The empowerment activity of the PKK Women's Group in Sambirejo Village aims to provide information, training and assistance regarding how to use durian peel waste into products that have a selling value and can reduce environmental waste. This activity received a positive response from the PKK Women's Movement and Village Apparatus in Sambirejo. From the results of this empowerment activity, the Sambirejo Village PKK Women's Group was able to process and utilize durian peel waste into a product that has a selling value.